Israel-Hamas war: the significance of the Holocaust - Farrow, Luca (2024)
As the Israel-Hamas war continues and the death toll of peaceful Palestinians continues to rise, there is an important drive to raise awareness of the history and plight of the Palestinian people. However, for a proper understanding of the conflict, there is also the need to explain the history of persecution of Jews, including the Holocaust, and how this has affected Israel and its allies.